Cervical Alignment of Anterior Cervical Hyperostosis Causing Dysphagia. Issue 5 (1st March 2019) - Kawamura, Ichiro; Tominaga, Hiroyuki; Tanabe, Fumito; Yamamoto, Takuya; Taniguchi, Noboru
Abstract : Study Design: Retrospective case control study. Objective: To investigate whether cervical alignment is related to dysphagia in patients with cervical diffuse idiopathic skeletal hyperostosis (DISH). Summary of Background Data: DISH involves a wide range of ligamentous ossifications, which can cause dysphagia. However, even patients with a high degree of ossification can have only mild dysphagia. Dysphagia results from esophageal compression due to ossification; however, the exact cause of dysphagia is unknown. Methods: We reviewed five patients with advanced dysphagia due to anterior cervical hyperostosis who underwent resection (S group), and five patients with mild symptoms who were only monitored (NS group). The patients were evaluated using the Eating Assessment Tool-10 (EAT-10) and plain kinetic radiographs of the cervical spine. The O–C2 angle, M–C angle, C2–7 angle, and C2–6a angle were measured in the flexion, neutral, and extension positions. We compared these parameters in the S group versus the NS group, and compared the pre- and postoperative values in the S group. Results: The EAT-10 score indicated a high degree of dysphagia in the S group preoperatively (25 [22–27]) compared with the NS group (1 [1–6]). In the S group, the EAT-10 score significantly decreased postoperatively to 1 (0–1), and improvement of dysphagia was observed. There was a significant difference between the S and NS groups in the ΔC2–7 and ΔC2–6a, and between pre- and postoperative values in the S group. There were no significant changes in O–C2 angle and M–C angle, which are parameters of the superior cervical vertebrae. Conclusion: The present results suggest that the restriction of flexion due to cervical spine ankylosis may be one of the reasons for dysphagia in patients with DISH. Level of Evidence: 4